Incentive Contracts and Efficient Unemployment Benefits in a Globalized World - Carsten Helm; Dominique Demougin (University of Oldenburg, Department of Economics, 2012)
Several European countries have reformed their labor market institutions. Incentive effects of unemployment benefits have been an important aspect of these reforms. We analyse this issue in a principal-agent model, higher level of unemployment benefits improves the workers' position in wage bargaining, leading to stronger effort incentives and higher output. However, it also reduces incentives for labor market participation. Accordingly, there is a trade-off. We analyze how changes in the economic environment such as globalization and better educated workers affect this trade-off.
Keywords: J65; D82; J41; E24; 330; Unemployment benefits; incentive contracts; Nash bargaining; moral hazard; globalization; Arbeitslosenversicherung; Ökonomischer Anreiz; Arbeitsmarktintegration; Moral Hazard; Asymmetrische Information; Nash-Gleichgewicht; Institutionelle Infrastruktur; Globalisierung; Prinzipal-Agent-Theorie